Psychological Dynamics of Incest Victims - Rizqina, Fathi; Paramastri, Ira (Universitas Muhammadiyah Surakarta, 2015)
Incest is any sexual activities between family members or relatives in which they are legally forbidden to marry each other. It is closely related to the experience of sexual abuse which brings psychological damage to the victim. The objective of this study was to figure out the psychological dynamics of the victims of incest, particularly in the case of daughters as the victim of incest committed by their fathers, which was represented by 2 (two) respondents. This study used a qualitative approach with a phenomenological method which was aimed to notice the real phenomenon. The actual cases of the phenomenon were studied whereas data collection was conducted through interview and observation. The analysis of data was carried out with Interpretative Phenomenological Analysis (IPA). The results showed that psychological dynamics of the victims could be assumed as both similar and dissimilar. The factors stimulated the activity were mostly similar, which were biological factor, economic factors, education factor, social and cultural environment factor, intention and opportunity factor, and family factors including parents’ characteristics. In addition, the psychological impact faced by both of the respondents was the feeling of anxiety, which was manifested in different ways. It might be caused diverse individual’s characteristic, perspective, view towards the abuser, as well as interpretation on sexual abuse.